Ecthyma gangrenosum in a patient with febrile pancytopenia - Samia Mrabat; Hanane Baybay; Ryme Dassouly; Zakia Douhi; Sara Elloudi; Fatima Zahra Mernissi (Our Dermatology Online, 2022)
Ecthyma gangrenosum (EG) is a cutaneous infection most commonly associated with Pseudomonas bacteremia and usually occurring in immunocompromised patients [1]. The infection progresses sequentially from a maculopapular rash to hemorrhagic bullae, then to necrotic ulcerations with surrounding erythema [2]. Herein, we report a case of ecthyma gangrenosum in an immunologically compromised patient. A 65-year-old female was admitted to the oncohematology department for febrile pancytopenia. Blood work revealed severe thrombocytopenia at 15,000/mm³), an absolute neutrophil count of 180 cells/mm³, and anemia. A sternal bone marrow puncture found 15% of plasma cells. Four days after the admission, the patient had a painful, quickly extending lesion on the abdomen. She described erythema that progressed to pustules, then ulcerations. On general clinical evaluation, the patient was feverish at 40°C. A dermatological examination revealed the presence of a 6 cm purpuric patch on the left flank with a central necrotic eschar (Fig. 1). The diagnosis of ecthyma gangrenosum was reached and the patient was treated with ceftazidime and vancomycin. Unfortunately, having gone into septic shock, the patient died one week later.